Proteome-wide analyses reveal diverse functions of protein acetylation and succinylation modifications in fast growing stolons of bermudagrass (Cynodon dactylon L.) - Bing Zhang; Zhuoting Chen; Qixue Sun; Jianxiu Liu (figshare, 2022)
Abstract Background Bermudagrass (Cynodon dactylon L.) is an important warm-season turfgrass species with well-developed stolons, which lay the foundation for the fast propagation of bermudagrass plants through asexual clonal growth. However, the growth and development of bermudagrass stolons are still poorly understood at the molecular level. Results In this study, we comprehensively analyzed the acetylation and succinylation modifications of proteins in fast-growing stolons of the bermudagrass cultivar Yangjiang. A total of 4657 lysine acetylation sites on 1914 proteins and 226 lysine succinylation sites on 128 proteins were successfully identified using liquid chromatography coupled to tandem mass spectrometry, respectively. Furthermore, 78 proteins and 81 lysine sites were found to be both acetylated and succinylated. Functional enrichment analysis revealed that acetylated proteins regulate diverse reactions of carbohydrate metabolism and protein turnover, whereas succinylated proteins mainly regulate the citrate cycle. These results partly explained the different growth disturbances of bermudagrass stolons under treatment with sodium butyrate and sodium malonate, which interfere with protein acetylation and succinylation, respectively. Moreover, 140 acetylated proteins and 42 succinylated proteins were further characterized having similarly modified orthologs in other grass species. Site-specific mutations combined with enzymatic activity assays indicated that the conserved acetylation of catalase and succinylation of malate dehydrogenase both inhibited their activities, further implying important regulatory roles of the two modifications. Conclusion In summary, our study implied that lysine acetylation and succinylation of proteins possibly play important regulatory roles in the fast growth of bermudagrass stolons. The results not only provide new insights into clonal growth of bermudagrass but also offer a rich resource for functional analyses of protein lysine acetylation and succinylation in plants.
Keywords: Biochemistry; Physical Sciences not elsewhere classified; Genetics; Environmental Sciences not elsewhere classified; Chemical Sciences not elsewhere classified; Ecology; Biological Sciences not elsewhere classified; Developmental Biology; Hematology; Plant Biology